3t-4(2t+1)=9(t-2)
3t - 8t - 4 = 9t - 18
18 - 4 = 9t - 3t + 8t
14 = 14t
t = 1
2007-06-13 13:48:28
·
answer #1
·
answered by Steve A 7
·
0⤊
0⤋
T=1
2007-06-13 13:51:25
·
answer #2
·
answered by Jethro 2
·
0⤊
0⤋
THIS IS THE CORRECT ANSWER!!!!
3t-8t-4=9t-18
-5t-9t=-18+4
-14t=-14
t=1
2007-06-13 13:51:44
·
answer #3
·
answered by viktor_08 2
·
0⤊
0⤋
3t-4(2t+1)=9(t-2)
3t - 8t - 4=9t-18
-5t-4=9t-18
-4+18=9t+5t
14=14t
1=t
2007-06-13 13:57:05
·
answer #4
·
answered by Kimchie 2
·
0⤊
0⤋
3t-4(2t+1)=9(t-2)
3t-8t-4 = 9t-18
-5t-4 = 9t - 18
-14t = -14
t =1
2007-06-13 13:49:44
·
answer #5
·
answered by beejin 4
·
0⤊
0⤋
3t - 8t - 4 = 9t - 18
14t = 14
t = 1
2007-06-14 02:08:47
·
answer #6
·
answered by Como 7
·
0⤊
0⤋
3t-8t-4=9t-18
-5t-4=9t-18
4t-4=-18
4t=-14
t=-14/4
2007-06-13 13:47:37
·
answer #7
·
answered by leo 6
·
0⤊
2⤋